Failure mechanism of soft– hard- interbedded rock slopes in cold regions: Numerical simulation and theoretical analysis - Lilong Ma; Runsen Lai; Zizhao Zhang; Yanyang Zhang; Qianli Lv; Guangming Shi; Junpeng Huang (PLoS ONE, 2025)
The soft– hard- interbedded rock slope in cold regions generally undergo the differential weathering due to the freeze-thaw effects, for which the irregular rock fractures increase the risk of geological disasters occurrence. To investigate the failure mechanism of the rock slope, both the numerical simulation and theoretical analysis were adopted in the present research. The structural integrity of the soft– hard- interbedded rock slope subjected to three different conditions (e.g., freeze-thaw cycles, natural, and anchored surroundings) was evaluated. The results indicated that the stability of the rock slope is significantly affected by the freeze-thaw cycles, the performance of which is much different from that under the natural- and anchored conditions. The failure process of the soft– hard- interbedded rock slope in cold regions exhibited the unloading-tensile cracking-sliding characteristics. The damage of the irregular structural surfaces subjected to the long-term weathering and freeze-thaw cycles is the one of the main factor controlling the failure mode. As revealed by numerical simulation, the application of the anchor rods can effectively prevent and control the collapse of the soft– hard- interbedded rock slope. The findings obtained from this research provide an important guidance for the stability assessment and mitigation design of the soft– hard- interbedded rock slopes in cold regions.